'It's a Wonderful life': a portrait of a man in crisis. (2nd July 2016) - Earl, Hank
Abstract : Drawing on the classic film It's a Wonderful Life and my own experience of participation in and facilitation of men's groups, this article seeks to appraise the central character's emotional range and intensity, charting parallels between George Bailey and Parsifal, the Grail Knight, whose story forms the spine of Robert A. Johnson's book He: Understanding Masculine Psychology (1991).